Endophytic xylariaceous fungi from rice in northern Thailand: discovery of novel species and new host records - Sahar Absalan; Alireza Armand; Ruvishika S. Jayawardena; Nakarin Suwannarach; Jutamart Monkai; Nootjarin Jungkhun; Saisamorn Lumyong; Kevin D. Hyde (MycoKeys)
Rice (Oryza sativa L.) is a major economic crop and a staple food in Asian countries, especially Thailand. Various fungi, including endophytes, are associated with rice and play a significant role in its growth and health. Endophytic xylarialean species are known for their diverse potential roles; however, limited information is available about this group of fungi in relation to rice. Two new species (Microdochium oryzicola and Nemania oryzae) and three new host records (Apiospora intestini, A. mukdahanensis, and Nemania primolutea) on rice are introduced in this study. Species identification was based on morphological characteristics and phylogenetic analyses of the combined internal transcribed spacers (ITS), 28S ribosomal RNA (LSU), RNA polymerase II second largest subunit (rpb2), β-tubulin (tub2), and translation elongation factor 1-alpha (tef1-α) loci. Descriptions, illustrations, and phylogenetic analysis results of the new species and new records are provided.